2007
DOI: 10.1143/jjap.46.l1240
|View full text |Cite
|
Sign up to set email alerts
|

Color Sensors with Three Vertically Stacked Organic Photodetectors

Abstract: A stacked structure composed of three organic photodetectors that were individually sensitive to only one of the primary color components was fabricated based on tetra(4-methoxyphenyl) porphine cobalt complex, NN 0 -dimethylquinacridone, or zinc phthalocyanine, as blue, green, or red sensitive photoconductive materials, respectively. The spectral photoresponse characteristics were measured, and the output signal from each detector showed good spectral selectivity, clearly demonstrating color separation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…[3][4][5][6] However, the transmittance of the thin metal based OPDs is low due to high reflectance of thin Au and Ag film. To solve this problem, various transparent conducting oxides (TCOs), such as indium tin oxide (ITO) [7][8][9][10] and indium zinc oxide (IZO), 11 have been used. The TCOs are mostly deposited by a sputtering process and a stable buffer layer must be formed between the TCO electrode and organic layers to protect the underlying organic layers from damage during the sputtering process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] However, the transmittance of the thin metal based OPDs is low due to high reflectance of thin Au and Ag film. To solve this problem, various transparent conducting oxides (TCOs), such as indium tin oxide (ITO) [7][8][9][10] and indium zinc oxide (IZO), 11 have been used. The TCOs are mostly deposited by a sputtering process and a stable buffer layer must be formed between the TCO electrode and organic layers to protect the underlying organic layers from damage during the sputtering process.…”
mentioning
confidence: 99%
“…The TCOs are mostly deposited by a sputtering process and a stable buffer layer must be formed between the TCO electrode and organic layers to protect the underlying organic layers from damage during the sputtering process. Amorphous carbon nitride (a-C:N), 7 naphthalene tetra carboxylic anhydride (NTCDA) , 8 and lithium fluoride (LiF) 9 have been used as buffer layers in transparent OPDs. However, the best performed transparent OPDs reported up to now exhibited the detectivity of 3.2 Â 10 11 cm Hz 1/2 /W at a reverse bias of À0.1 V, 6 which is poorer than the conventional OPDs with highly reflective metal electrodes which show about $10 12-13 cm Hz 1/2 /W, [12][13][14][15][16] probably due to the inappropriate thickness and type of buffer layer.…”
mentioning
confidence: 99%
“…1͑a͒. [15][16][17] This might change full-color digital image sensors smaller, more lightweight, and higher resolution. 16 In the case of layer-stack type image sensors, we need to consider the order of the subcells for each primary color of light.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] This might change full-color digital image sensors smaller, more lightweight, and higher resolution. 16 In the case of layer-stack type image sensors, we need to consider the order of the subcells for each primary color of light. From the viewpoint of physical chemistry of organic materials, red-light sensitive subcells ͑R-cells͒, of course, mainly absorb red light but also slightly absorb blue and green lights fundamentally because red-light-absorbing molecules must have other electronic transitions due to higher excite states.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to realize in the case of single layer structures. This fact causes lower external quantum efficiencies (EQEs) of solution-processed devices than those of multilayer structures fabricated by conventional thermal evaporation method [7]. By now, our research group reported an improved photoconductive characteristics of blue-sensitive organic devices by doping silole derivatives into poly(dioctylfluorenylco-benzo-thiadiazole (F8BT) [8,9].…”
mentioning
confidence: 99%